Application Of Service Excellent In Increasing Member Loyalty At BMT NU Giliraja - Riyanti Riyanti; Aidil Aminah (Universitas Islam Darul 'ulum Lamongan, 2026)
This study examines the application of service excellence in improving member loyalty at BMT NU Giliraja, a community-based Islamic microfinance institution in Sumenep Regency, East Java. The institution faces challenges in maintaining member loyalty, with declining member participation and an increase in non-performing loans. This study employs a descriptive qualitative approach using data collection techniques such as in-depth interviews, non-participatory observation, and internal documentation. The research focuses on analyzing how the dimensions of service excellence-including responsiveness, empathy, transparency, and Islamic values-contribute to member loyalty. The main findings indicate that member loyalty is more influenced by personal interactions based on religious and social values than by physical facilities or technical services. Service speed, empathetic attitudes of staff, transparency of information, and service innovations such as pickup deposits and WhatsApp are dominant factors in building loyalty. Practically, this study suggests that BMT NU Giliraja needs to strengthen staff soft skills training and continue digital service innovations to expand access without reducing personal closeness. Theoretically, this study enriches the literature on service excellence in community-based Islamic microfinance institutions and contributes to the development of Islamic economics and Islamic education in the future.